Evaluation of the degree of metabolic compensation and prevalence of diabetic complications in a Russian population of childrenand adolescents (results of the ?Screening for diabetic complications and assessment of medical aid to diabetic patients? Project) - Ekaterina Andreevna Andrianova (Endocrinology Research Centre, 2009)
Aim. To analyse the degree of compensation of disturbed carbohydrate metabolism and to evaluate its effect on the prevalence of diabetic complicationsin children and adolescents from 20 regions of RF. Materials and methods. A total of 2984 patients with DM1 were examined in 2002-2005 including 1532 children below 14 yr and 1452 adolescentsof 15-17 yr. The patients were selected from regional DM registries by the random number method. Results. Mean HbA1с was 9,77?2,30%. The number of children with compensated carbohydrate metabolism at the time of screening was significantlyhigher than that of adolescents (21,1 and 15,1% respectively, p